Killer Whales (Orcinus orca) Chasing Gray Whales (Eschrichtius robustus) in the Northern Bering Sea - Ljungblad, Donald K.; Moore, Sue E. (ARCTIC, 1983)
Sixteen killer whales (Orcinus orca) were observed for 90 minutes as they approached and then chased gray whales (Eschrichtius robustus) in the Bering Sea north of St. Lawrence Island, Alaska. The killer whales swam in four discrete lines that blew synchronously as they approached an area in which gray whales were feeding. Once in the gray whales' feeding area, the killer whales broke into small groups and dispersed. The gray whales, which had been dispersed while feeding, formed groups of three to six and swam away from the killer whales, except for one individual. That whale was pursued by four killer whales swimming nearly abreast in a loose crescent formation with about 300 m between individuals. Although a sonobuoy was deployed throughout the observation period, no sounds were recorded from either species. The absence of whale sounds raises questions about how the whales detected one another and communicated between nearby conspecifics.Key words: killer whale (Orcinus orca), gray whale (Eschrichtius robustus), Bering Sea, predator/prey, acoustics Mots clés: épaulard (Orcinus orca), baleine grise de Californie (Eschrichtius robustus), mer de Béring, prédateur/proie, acoustique